2023
DOI: 10.3390/su15097024
|View full text |Cite
|
Sign up to set email alerts
|

Why Gender Matters in Breeding: Lessons from Cooking Bananas in Uganda

Abstract: This study examined the gender-differentiated trait preferences of cooking banana (matooke) for farmers and consumers in Central Uganda to inform banana-breeding strategies. Women and men banana farmers might have differing production objectives, norms, and values which drive decisions on which varieties to adopt and grow. However, breeders rarely consider this in their variety development programs, leading to lost opportunities for equitable breeding. An exploratory sequential mixed-method approach was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In terms of gender, more men compared to women prefer high yielding varieties, and this is consistent with the finding by Nchanji et al (2021) who reported that men tend to adopt and grow better yielding improved varieties while women tend to grow landraces with low yields. This difference in preferences highlights the diverse roles and responsibilities of men and women in agriculture, influencing their distinct criteria for selecting finger millet varieties (Tufan et al, 2018;Weltzien et al, 2019;Sanya et al, 2020Sanya et al, , 2023Marimo et al, 2021;Zimba et al, 2023). Although there was no significant difference in other traits considered during the production of finger millet, it's evident that similar traits are prioritized differently by men and women.…”
Section: Finger Millet Varietal and Trait Preferences Across Regions ...mentioning
confidence: 98%
See 2 more Smart Citations
“…In terms of gender, more men compared to women prefer high yielding varieties, and this is consistent with the finding by Nchanji et al (2021) who reported that men tend to adopt and grow better yielding improved varieties while women tend to grow landraces with low yields. This difference in preferences highlights the diverse roles and responsibilities of men and women in agriculture, influencing their distinct criteria for selecting finger millet varieties (Tufan et al, 2018;Weltzien et al, 2019;Sanya et al, 2020Sanya et al, , 2023Marimo et al, 2021;Zimba et al, 2023). Although there was no significant difference in other traits considered during the production of finger millet, it's evident that similar traits are prioritized differently by men and women.…”
Section: Finger Millet Varietal and Trait Preferences Across Regions ...mentioning
confidence: 98%
“…Probit model results revealed that gender, marital status, education levels, and occupation are the major socio-demographic factors that influence specific preferences related to the cultivation of finger millet. Gender-related differences in preferences arise from the different roles and responsibilities within households (Sanya et al, 2023;Zimba et al, 2023). Female farmers prioritized millet varieties with big grain size, taste, and ease of cultivation, differently from their male counterparts who prefer varieties that are high yielding, and drought tolerant.…”
Section: Socio-demographic Factors That Influence Finger Millet Prefe...mentioning
confidence: 99%
See 1 more Smart Citation
“…[11,17] Poor agronomic practices [19] Land use changes by urbanization [19] Labor shortages [19] Banana is mostly produced in three regions of the country, the southwestern, central, and eastern regions [4]. Until the 1990s the central region had been the main banana-producing area, yet the production moved gradually to the west-south where the crop is now grown more commercially [3,22,23]. A study finds 85% of the sampled farms in the southwestern region sold bananas, compared to around 45% in the central and eastern regions [24].…”
Section: Some Factors Associated With Banana Productivity Referencementioning
confidence: 99%
“…From the agronomic perspective, key characteristics frequently mentioned are bunch size, finger size, cultivar longevity, marginal soil tolerance, early maturity, drought tolerance, pest resistance, toppling, marketability, appearance, stem sturdiness, and planting material availability. From the consumption perspectives, they include yellow color, homogeneity of the color, moistness, smoothness, moldability, taste, and aroma [2,10,23,31]. Popular local varieties tend to possess some superior qualities both in the agronomic and consumption characteristics, yet no single cultivar meets all preference criteria [10].…”
Section: Banana Varieties and Hybrid Adoptionmentioning
confidence: 99%